Involvement of mitochondria in changes in fluorescein excitation and emission polarization spectra in living cells. - Cercek, L (1979)
The comparison of fluorescein polarization spectra in living cells and in isolated subcellular structures identified the mitochondria as the cytoplasmic domain in which on excitation at 470 nm the sharp fluorescein emission polarization peak at 510 nm is formed. Changes in the emission polarization peak during the cell cycle or those induced by growth stimulators and inhibitors reflect structural changes in the mitochondria on their transition from the resting, orthodox into the active, ATP-generating, condensed conformation and vice versa. Possible mechanisms for the formation of the sharp emission polarization peak are discussed.